Osteogenesis Imperfecta: Case Report and Literature Review - I Gede Bramantya Surya Mahendra; Dyah Purnaning (Jurnal Penelitian Pendidikan IPA, 2024)
Osteogenesis imperfecta or brittle bone disease is a disorder of congenital bone fragility caused by genetic mutations in the procollagen type 1 code (COL1A1 and COL1A2). The global prevalence of children born with osteogenesis imperfecta is estimated to be 1 in 100,000 children worldwide. The diagnosis of osteogenesis imperfecta is based on history taking, physical examination, and supporting examination. Management of patients with osteogenesis imperfecta requires multidisciplinary treatment. There are several treatments that can be done, including conservative management, surgical management, and medical rehabilitation. This case report will discuss an 8-year-old girl who was treated at the West Nusa Tenggara Provincial Hospital with a diagnosis of closed fracture of the sinistra femur, osteogenesis imperfecta, and Congenital Talipes Equinovarus (CTEV).